Characteristics and aspiration of entrepreneurship among student teachers of Teacher Education Institute, Technical Education Campus (IPGKPT) - Romy bin Abd Kadir; B. A. Ajurun; Nurain Baharin; Mohd Ridzuan bin Padzil; Hanani Binti Harun Rasit; Abd Hadi; T. Shanmugam; Shaharudin Shaharudin; B. Janain (Jurnal Pendidikan Vokasi, 2024)
Entrepreneurship education programmes have been expanded globally across multiple levels of education to foster entrepreneurial competencies, including among student teachers at the Technical Education Campus, Teacher Education Institute (IPGKPT). Despite this development, limited studies have examined the entrepreneurial mindset of future teachers, who play a crucial role in shaping the next generation. This study aims to identify the entrepreneurial characteristics and the level of entrepreneurial aspirations among IPGKPT student teachers. A descriptive quantitative survey design was employed, involving 498 student teachers who responded to a Likert-scale questionnaire distributed via Google Forms. The results indicated that entrepreneurial characteristics (M = 3.78, SD = 0.85) and entrepreneurial aspirations (M = 3.76, SD = 0.85) were both at a high level. The findings further showed that student teachers demonstrated strong traits in risk-taking, innovativeness, and locus of control, as well as high levels of achievement motivation and self-efficacy. These results suggest that student teachers at IPGKPT are well-prepared to embrace entrepreneurship education and may potentially become role models in fostering entrepreneurial culture in schools. The study highlights the importance of sustaining and strengthening entrepreneurship education programmes in higher education institutions, particularly in teacher training colleges, to equip future educators with entrepreneurial mindsets and competencies. Such initiatives are expected to enhance graduate employability, encourage innovation in teaching, and contribute to broader national efforts toward economic growth and sustainability.